Growth differentiation factor 11 suppresses intrahepatic inflammation via restricting NLRP3 inflammasome activation in LPS-induced liver injury: GDF11 alleviates acute liver injury - Huang, Hui; Wu, Shengyi; Yan, Yawei (Cellular and Molecular Biology, 2023)
Growth differentiation factor 11 (GDF11) is reported as a member of TGF-β superfamily, which plays a key negative role in various tissue inflammation. However, the specific effect of GDF11 on infectious acute liver injury remains unknown. The current study is designed to certify the role of GDF11 both in LPS-induced RAW 264.7 cell line and rodent model of acute liver injury (ALI) and further investigate its molecular mechanism of inflammatory regulation. In vitro, LPS was used to stimulate the inflammatory activation of RAW 264.7 cells and then recombinant GDF11 (rGDF11) was used to treat the cells. In vivo, we injected LPS and rGDF11 in abdomen of mouse. The inflammatory indexes, GDF11 level, NLRP3 level, liver tissue injury, and liver function were examined using qRT-PCR, western blot, ELISA, IHC, IF and HE staining, respectively. Supplement of GDF11 protected the histology and function of liver tissue in LPS-induced ALI mice, in which the level of AST, ALT and TBiL associated with tissue damage were reduced after ALI. Moreover, increased GDF11 in RAW 264.7 cells and ALI mice reduced the expressions of COX-2, TNF-α, IL-1β, and IL-6 via inhibiting NLRP3 inflammasome activation, suggesting the anti-inflammatory role of GDF11 in ALI. Besides, owing to the protective role of GDF11, the apoptotic degree in liver after LPS insult was attenuated, such as the reduced c-caspase-3 and annexin-V expressions. The results indicate that overexpression of GDF11 plays an antagonistic role in LPS-induced inflammatory response after ALI. Therefore, GDF11 may become a promising target for preventing infectious acute liver injury.